A COMPETENCE APPROACH IMPLEMENTED IN TRAINING OF FUTURE PILOTS AT HIGHER EDUCATION MILITARY INSTITUTES TO APPLY PROFESSIONAL KNOWLEDGE INTO PRACTICE - Nevzorov, Roman (Proceedings of National Aviation University, 2018)
Issue definition: The experience in student pilots’ training in the professional education system confirms that education goals and essence should be reconsidered. The purpose of the research is to substantiate organizational and pedagogical conditions of competency development in student pilots’ training. Materials and methods of the research: The research methodology is based on philosophical ideas about the unity of pilot’s personal and professional development; certain provisions of the information theory; principles of the theory and practice unity, democratization of military education. Methods of the research: theoretical; empirical; mathematical statistics. The results: The philosophical, scientific and psychological and pedagogical literature was analyzed in our research. Different approaches to understanding the competence approach and to understanding "competence" and "expertise" terms were clarified. These concepts are revealed not have a single definition or hierarchical component. The study of theoretical issues of the competence approach in pedagogy and the competence place in the pedagogical process has revealed that the competence approach is being intensively studied and serves as a basis for the educational process at higher military educational institutes. It is determined that the pedagogical process is based on the competence approach, involving development of different types of students’ competences. Pedagogical aspects of development of student pilots’ competence at HEMIs have been studied. It has been determined which teaching stages and steps of contribute to development of students’ competences at the military educational institutes of the Ukrainian Air Force. Conclusions: The idea of competence education is one of the responses of the education system to global transformations in the international community.